Constructs of the Health Belief Model as Predicting Factors in Breast Self-Examination - L Hasani; T Aghamolaei; SS Tavafian; Sh Zare (Tehran University of Medical Sciences, 2011)
Background & Aim: Early diagnosis of breast lumps through breast self-examination (BSE) is important for early detection of breast cancer. The aim of this study was to evaluate factors predict the BSE behavior using Health Belief Model constructs in women referred to health centers in Bandar abbas, Iran. Methods & Materials: In this cross-sectional study, 240 eligible women were randomly selected from eight health centers. Data were collected using a self-administered questionnaire including demographic characteristics and Champion's Health Belief Model Scale (CHBMS). The CHBMS measures the HBM concepts of susceptibility (3 items), seriousness (6 items), benefits (4 items), barriers (8 items) and self-efficacy (10 items). All items were ranged in a Likert scale ranging from ‘‘strongly disagree (score: one)'' to ‘‘strongly agree (score: five)''. Results: A total of 240 women took part in the study. The mean age of participants was 37.2 (SD=6.1). Of all, 32.5% had high school education; and 95.8% were married. The results showed that 31.7% of the women had performed the BSE; however, only 7.1% had performed it regularly. Perceived BSE benefits, perceived BSE barriers and perceived BSE self-efficacy of the participants who performed the BSE were significantly higher than those who did not (P<0.03). The results from regression analysis indicated that the perceived BSE self-efficacy and perceived BSE barriers predicted breast self-examination behavior (P<0.001). Conclusion: The findings of this study indicated that perceived BSE barriers and perceived BSE self-efficacy were influencing factors in predicting the BSE behavior. Therefore, in order to improve self-efficacy and decrease the barriers, BSE training programs are strongly recommended.   Key words: Health belief model, Prediction, Breast self-Examination, Breast Cancer, Bandar Abbas, Iran